“ Japan-China relations after 2020 from interdependence to balance of interests" - Ali Hussein Al-esami (Tikrit Journal For Political Science, 2026)
This research highlights the elements and variables that affecting the nature of Japanese-Chinese relations through testing the Randall Schuler's assumptions of balance of interests theory, and how it can contribute to explaining and predicting the future paths of cooperation and competition between them. It addresses the most prominent determinants facing Japanese-Chinese relations and measuring its impact, as well as tracking the ranges of trade partnership since the Regional Comprehensive Economic Partnership Agreement (RCEP) came into effect in 2021, which represents the first regional trade partnership agreement that brings them together, and how it can contribute to setting limits for security competition and enhance opportunities for cooperation between them.